Light Sampling via Throttled Visual Phototransduction Robustly Synchronizes the Drosophila Circadian Clock. - Ogueta, M.; Hardie, R.C.; Stanewsky, R. (Current Biology, 2020)
The daily changes of light and dark exemplify a prominent cue for the synchronization of circadian clocks with the environment. The match between external and internal time is crucial for the fitness of organisms, and desynchronization has been linked to numerous physical and mental health problems. Organisms therefore developed complex and not fully understood mechanisms to synchronize their circadian clock to light. In mammals and in Drosophila, both the visual system and non-image-forming photoreceptors contribute to circadian clock resetting. In Drosophila, light-dependent degradation of the clock protein TIMELESS by the blue light photoreceptor Cryptochrome is considered the main mechanism for clock synchronization, although the visual system also contributes. To better understand the visual system contribution, we generated a genetic variant exhibiting extremely slow phototransduction kinetics, yet normal sensitivity. In this variant, the visual system is able to contribute its full share to circadian clock entrainment, both with regard to behavioral and molecular light synchronization. This function depends on an alternative phospholipase C-? enzyme, encoded by PLC21C, presumably playing a dedicated role in clock resetting. We show that this pathway requires the ubiquitin ligase CULLIN-3, possibly mediating CRY-independent degradation of TIMELESS during light:dark cycles. Our results suggest that the PLC21C-mediated contribution to circadian clock entrainment operates on a drastically slower timescale compared with fast, norpA-dependent visual phototransduction. Our findings are therefore consistent with the general idea that the visual system samples light over prolonged periods of time (h) in order to reliably synchronize their internal clocks with the external time.